Endovascular coil embolization for accessory veins in dialysis AVF: A pioneering case series from Saiful Anwar Hospital, Malang - Fahmi, Hanim Isyfi; Kurnianingsih, Novi (Universitas Brawijaya, 2025)
Background: The optimal vascular access for hemodialysis is an arteriovenous fistula (AVF), yet the failure rates range from 30% to 40%. Accessory veins modify blood flow, contributing to 40% of early failures. The treatment for stenosis is clearly established, whereas accessory vein treatment is not. Case Illustration: Two cases of endovascular coil embolization for accessory vein obliteration were performed at Saiful Anwar Hospital, Malang. The first case involved a 47-year-old female with late arteriovenous fistula failure, which was fixed with a percutaneous transluminal angioplasty and coil embolization. The second case involved a 58-year-old male with early radiocephalic arteriovenous fistula failure, which was also treated with a percutaneous transluminal angioplasty and coil embolization. Both procedures achieved complete elimination of the accessory vein and showed no signs of retrograde flow. The first and second cases have different onsets of early and late failure. Both patients required PTA and coil embolization simultaneously. Conclusion: Endovascular coil embolization is a safe and effective technique for occluding accessory veins in AVF, which helps improve their function in both early and late failures and shows higher success rates.